2014
DOI: 10.1371/journal.pone.0092728
|View full text |Cite|
|
Sign up to set email alerts
|

Excessive Nitrite Affects Zebrafish Valvulogenesis through Yielding Too Much NO Signaling

Abstract: Sodium nitrite, a common food additive, exists widely not only in the environment but also in our body. Excessive nitrite causes toxicological effects on human health; however, whether it affects vertebrate heart valve development remains unknown. In vertebrates, developmental defects of cardiac valves usually lead to congenital heart disease. To understand the toxic effects of nitrite on valvulogenesis, we exposed zebrafish embryos with different concentrations of sodium nitrite. Our results showed that sodiu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 39 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…To observe the morphology and count heart rates, we treated embryos with 0.04 mg/ml MS-222 (Sigma) at room temperature for 5 min and then mounted them with 3% methyl cellulose (Sigma). To examine the EI, we measured the distance from the heart center to the heart boundary (a) and from the heart center to the pericardium (b), as reported previously (28). The EI was calculated by the expression, b/a.…”
Section: Live Imaging and Quantificationmentioning
confidence: 99%
“…To observe the morphology and count heart rates, we treated embryos with 0.04 mg/ml MS-222 (Sigma) at room temperature for 5 min and then mounted them with 3% methyl cellulose (Sigma). To examine the EI, we measured the distance from the heart center to the heart boundary (a) and from the heart center to the pericardium (b), as reported previously (28). The EI was calculated by the expression, b/a.…”
Section: Live Imaging and Quantificationmentioning
confidence: 99%
“…Work in zebrafish suggests that correct endocardium formation is exquisitely sensitive to NO. Embryos exposed to high nitrite concentrations form a normal vascular network and chamber endocardium but develop specific defects in the valve leaflets [73] .…”
Section: Role Of Mechanical Forces In Endocardium Development and Valmentioning
confidence: 99%
“…To understand the toxic effects of nitrite on human heart, Li exposed zebrafish embryos to different concentrations of sodium nitrite, their results showed that sodium nitrite caused the developmental defects of zebrafish heart dose-dependently. [18] In recent years, Penicillium spp. pigments have attracted the attention of researchers.…”
Section: Introductionmentioning
confidence: 99%